2020
DOI: 10.1002/anie.202013183
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder Polymer Networks with Temperature‐Reversible Cross‐Linking‐Induced Emission

Abstract: A novel synthetic strategy gives reversible crosslinked polymeric materials with tunable fluorescence properties. Dimaleimide-substituted tetraphenylethene (TPE-2MI), which is non-emissive owing to the photo-induced electron transfer (PET) between maleimide (MI) and tetraphenylethene (TPE) groups, was used to cross-link random copolymers of methyl (MM), decyl (DM) or lauryl (LM) methacrylate with furfuryl methacrylate (FM). The mixture of copolymer and TPE-2MI in DMF showed reversible fluorescence with "on/ of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 40 publications
(12 reference statements)
0
43
0
Order By: Relevance
“…Similarly, para‐hydroxy‐TPE (TPE‐OH) reacted with 1,12‐dibromododecane to form TPE‐C 12 Br [22] . In the presence of TiCl 4 and zinc dust, McMurry coupling of BP‐C 4 Br and BP‐C 8 , and BP‐C 8 Br and BP‐C 4 could produce C 8 ‐TPE‐C 4 Br and C 4 ‐TPE‐C 8 Br [23] . Their molecular structures were verified using 1 H nuclear magnetic resonance ( 1 H NMR) spectra (Supporting Information, Figures S2–S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, para‐hydroxy‐TPE (TPE‐OH) reacted with 1,12‐dibromododecane to form TPE‐C 12 Br [22] . In the presence of TiCl 4 and zinc dust, McMurry coupling of BP‐C 4 Br and BP‐C 8 , and BP‐C 8 Br and BP‐C 4 could produce C 8 ‐TPE‐C 4 Br and C 4 ‐TPE‐C 8 Br [23] . Their molecular structures were verified using 1 H nuclear magnetic resonance ( 1 H NMR) spectra (Supporting Information, Figures S2–S4).…”
Section: Resultsmentioning
confidence: 99%
“…[22] In the presence of TiCl 4 and zinc dust, McMurry coupling of BP-C 4 Br and BP-C 8 ,and BP-C 8 Br and BP-C 4 could produce C 8 -TPE-C 4 Br and C 4 -TPE-C 8 Br. [23] Their molecular structures were verified using 1 Hn uclear magnetic resonance ( 1 HNMR) spectra (Supporting Information, Figures S2-S4). Thereafter,t hree bromine-functionalized intermediates (C 8 -TPE-C 4 Br,C 4 -TPE-C 8 Br, and TPE-C 12 Br) were reacted with excess trimethylamine to afford three target products:C 8 -TPE-C 4 TAB, C 4 -TPE-C 8 TAB, and TPE-C 12 TAB.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of the functionalized pre-polymers may be carried out by co-polymerization with a furan-or maleimide containing monomers. These approaches were widely used in recent investigations for the preparation of cross-linked polyurethanes [103], polyacrylates [42,104,105] (including photoactive polymers [106,107]), cross-linked polysaccharides [108], and other types of CANs. Linear polymers containing C2,C5-disubstituted furans as repeated units also can undergo cross-linking with bis-maleimides [109][110][111][112][113].…”
Section: Synthesis Of Cross-linked Dynamers Using the Fmda "Click" Reactionmentioning
confidence: 99%
“…A comparison of the rate of coupling for some fmDA adducts has shown that the efficiency of thermal and mechanical activation is not equal and depends on the regio-and stereo structure of the adducts: some diastereomers can be mechano-resistant due to misalignment of the dynamic DA bonds with the force vector providing ineffective mechanochemical interactions [147]. Besides thermal initiation, rDA reaction in CANs can be driven by other stimuli, such as light [107], mechanical [138] or magnetic force [139]. Light-responsive CANs based on a photocontrolled DA reaction could be obtained by the introduction of the fluorescent fragment into diene or dienophile [107,140,141].…”
Section: Synthesis Of Cross-linked Dynamers Using the Fmda "Click" Reactionmentioning
confidence: 99%
“…[14] Diels-Alder (DA) reaction is a cycloaddition reaction with "click" characteristics, which shows reversibility at high temperature of around 110 °C. [15] For these reasons, in the current work, we combine imine and DA reversible covalent bonds to design and synthesize double cross-linked gelatin hydrogels with integrated multiple functions: tough yet biocompatible, thermostable yet degradable, durable yet self-healing, acid/alkali resistance and organic solvents tolerance. The presence of double imine/DA connections further increase the cross-linking of such double network DN, hydrogels, meanwhile, introduced good thermostability, adjustable mechanical strength (up to 136 kPa), acid/alkali resistance at 65 °C and good integrity in DMF and DMSO solvents at 130 °C.…”
mentioning
confidence: 99%